Cleaner Core - Ayman Dwikat; Zaid Saad Al-Din. (My University, 2024)
These days, due to the increase and large size of buildings, many people suffer from the cleaning process, whether in large halls or in their homes, and due to the great development in technology and the emergence of new technologies, people are looking for alternatives to save time and effort. Our project is a robot whose function is to clean the floor so that it consists of two sides, the first side, which is the front side, so that it contains a vacuum cleaner to clean the dirt and the back side contains mops to polish the floor. The robot works automatically, the user just needs to put it in one of the corners of the room and then turn it on and then start cleaning the floor, and because it works automatically, we made it stay away from the objects that are in the room during the cleaning process. It can also be controlled remotely via a mobile phone, and if the robot is placed to clean a specific area, for example a room two meters by two meters, it will clean it completely and then stop automatically. Therefore, the main goal of our project is to design robots to clean the floor to save time and effort for people.